Liquid nitrogen cryotherapy effectively and safely improves response of thick actinic keratoses lesions by 5-aminolevulinic acid-based photodynamic therapy: A randomized, prospective, single-blind trial - Hongying Chen; Shuang Jin; Jiaan Zhang; Chao Luan; Mei Ju; Ronglin Zhang; Xiaohua Zhang; Yan Zhu; Lili Wang; Chen Zhuang; Dan Huang; Yu Hu; et al. (Photodiagnosis and Photodynamic Therapy, 2024)
Background: Actinic keratoses (AK) may progress into squamous cell carcinoma. Many combination therapies were used to improve the clearance rate. However, there are limited studies on the efficacy and safety of lesion-directed Liquid nitrogen cryotherapy combined with field-directed photodynamic therapy (PDT). Objective: This study is aimed to determine the efficacy and safety of Liquid nitrogen cryotherapy combined with PDT in Chinese patients with actinic keratosis. Methods: A total of 61 patients with AK were selected at the Institute of Dermatology, Chinese Academy of Medical Sciences and Peking Union Medical College between August 2018 and August 2023. They were randomly divided into PDT plus Liquid nitrogen cryotherapy group (LN-PDT) and control PDT group (C-PDT) with 30 patients and 31 patients, respectively. 27 patients in the LN-PDT group and 28 patients in the C-PDT group completed the clinical sessions. Efficacy, adverse effects, and cosmetic outcomes were recorded and compared between the two groups. Results: 3 months after the final treatment, the clearance rates for total AK lesions were 97.4 % (449/461) in the LN-PDT group and 93.4 % (456/488) in the C-PDT group (P < 0.05). For grade I AK lesions, the clearance rates were 99.2 % (234/237) for the LN-PDT group and 98.3 % (237/241) for the C-PDT group (P >0.05). For grade II lesions, the clearance rates were 97.5 % (156/160) for the LN-PDT group and 91.9 % (172/186) for the CPDT group (P < 0.05). For grade III lesions, the clearance rates of the LN-PDT and C-PDT groups were 87.5 % (58/64) and 78.7 % (47/61), respectively (P < 0.05). The two groups had no significant differences in pain, erythema, edema, hyperpigmentation and scarring. Cosmetic outcomes mainly were excellent or good in both groups with no significant difference. Conclusion: Liquid nitrogen cryotherapy combined with PDT showed higher efficacy on grade II and grade III AK lesions than PDT alone. The two groups have similar adverse effects and cosmetic outcomes.